2019
DOI: 10.1177/0117196819832721
|View full text |Cite
|
Sign up to set email alerts
|

The transformation of the primary health care system for Syrian refugees in Turkey

Abstract: This article analyzes Turkey's policy response to the health needs of Syrian refugees since 2011. The innovations in immigration health policy cannot be explained solely on the basis of factors exogenous to the health sector, such as the massive arrival of Syrian refugees, the gradual Europeanization of Turkish immigration policy or new funding from the European Union. They also display several stages of endogenous learning driven by a reassessment of problems and reevaluation of preferences by Turkish authori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The provision of chronic health services for Syrian refugees is the responsibility of AFAD. With the establishment of the Family Medicine model under the HTP came the development of family health centers that served as the main provider of primary health services for Syrian refugees [31]. In 2015, additional health facilities called Migrant Health Centers were established to provide further support for the Syrian refugee population, particularly in areas densely populated with Syrian refugees.…”
Section: Resultsmentioning
confidence: 99%
“…The provision of chronic health services for Syrian refugees is the responsibility of AFAD. With the establishment of the Family Medicine model under the HTP came the development of family health centers that served as the main provider of primary health services for Syrian refugees [31]. In 2015, additional health facilities called Migrant Health Centers were established to provide further support for the Syrian refugee population, particularly in areas densely populated with Syrian refugees.…”
Section: Resultsmentioning
confidence: 99%
“…17 Refugee health professionals can serve on steering groups to contribute cross-cultural knowledge to mentorship and placement programmes. 45 Work on regional accreditation by the East African Community could increase circular mobility of both South Sudanese and Ugandan migrants and refugees. 25 Advocacy action is needed to draw attention to the exclusion from and underutilisation of refugees in the health system.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the parameters related to the quality of life, we found that having primary care experience, having knowledge about the Turkish health system, believing that they can adapt to work in refugee health centers and not having a plan to return to their country were found to be associated with a higher score in at least one of the WHOQoL-BREF sub-domains. The fact that the health system in Turkey has been transformed in line with the needs of Syrian immigrants is likely to be one of the reasons for these results [21]. In this context, primary health care services, which are among the priority health needs of immigrants, were given priority, and Syrian refugee physicians were allowed to work primarily in refugee health centers [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the health system in Turkey has been transformed in line with the needs of Syrian immigrants is likely to be one of the reasons for these results [21]. In this context, primary health care services, which are among the priority health needs of immigrants, were given priority, and Syrian refugee physicians were allowed to work primarily in refugee health centers [21,22]. In a recent study on refugee physicians in Turkey, it was reported that refugee physicians, de ned as skilled refugees, have challenges in getting medical license equivalency, and the employment of specialists from various branches as GPs can lead to deskilling or overquali ed employment [3].…”
Section: Discussionmentioning
confidence: 99%